Why Wait? A Century of Life Before IPO - Jovanovic, Boyan; Rousseau, Peter L (American Economic Review, 2001)
Firms that entered the stock market in the 1990s were younger than any earlier cohort since World War I. Surprisingly, however, firms that IPO'd at the close of the 19th century were just as young as the companies that are entering today. We argue here that the electrification-era and the IT-era firms came in young because the technologies that they brought in were too productive to be kept out very long. The model assumes that the stage before IPO is a learning period during which the firm refines the idea before committing to it at the IPO stage. The better the idea, the higher is the opportunity cost of a delay in its implementation, and the earlier the firm will have its IPO.